Some Geopolitical Aspects Of The Development Of International Transport Corridors And Their Impact On Central Asia (Zien Journal of Social Sciences and Humanities, 2025)
The article is devoted to the analysis of geopolitical aspects of the development of international transport corridors (ITC) and their impact on the countries of Central Asia. The article examines current trends in global trade and transregional logistics caused by geopolitical instability, crises of traditional routes and strategic rivalry of world powers. Particular attention is paid to land transport arteries, such as the China-Kyrgyzstan-Uzbekistan international transport corridors and the Trans-Caspian route, which are acquiring strategic importance for diversifying supplies and reducing transport risks. The article analyzes the economic, political and infrastructural challenges facing the Central Asian states, as well as the prospects for integrating the region into global logistics chains. It is concluded that the successful implementation of transport corridors requires a combination of economic feasibility, geopolitical strategy and international cooperation